2018
DOI: 10.1016/j.idcr.2018.e00422
|View full text |Cite
|
Sign up to set email alerts
|

Nocardia paucivorans brain abscess. Clinical and microbiological characteristics

Abstract: HighlightsBrain abscess caused by Nocardia paucivorans is an infrequent infection in humans.Molecular speciation has revolutionized the study of Nocardia spp. infections.N. paucivorans brain abscess has a favourable prognosis with long-term antimicrobial therapy.Antimcirobial susceptibility testing is a useful guide to therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…N. paucivorans was first isolated in sputum in 2000 [ 58 ]. To our knowledge, 49 cases of N. paucivorans infection have been published [ 2 , 3 , 4 , 56 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ], and we summarize these in Table 1 . The majority (33 cases) were reported by Gray et al from Queensland, Australia, and were identified retrospectively via 16S ribosomal DNA sequencing of archived biopsy specimens [ 63 ].…”
Section: Literature Review and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…N. paucivorans was first isolated in sputum in 2000 [ 58 ]. To our knowledge, 49 cases of N. paucivorans infection have been published [ 2 , 3 , 4 , 56 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ], and we summarize these in Table 1 . The majority (33 cases) were reported by Gray et al from Queensland, Australia, and were identified retrospectively via 16S ribosomal DNA sequencing of archived biopsy specimens [ 63 ].…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…Unfortunately, the paper by Gray et al lacks details regarding therapy and outcome of most patients, limiting the information to be gained from these cases. Additionally, none of the 49 previously reported cases included detailed information on the presumed route of acquisition of N. paucivorans infection [ 2 , 3 , 4 , 56 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ].…”
Section: Literature Review and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prolonged use of corticosteroids, organ transplantation, the presence of cancer and human immunodeficiency virus infection are considered to be the most common predisposing factors for nocardial infections (nocardiosis) [ 2 ]. When nocardial infection occurs, species such as N .…”
Section: Case Reportmentioning
confidence: 99%
“…However, Nocardia species are also capable of disseminating from the primary site of infection, such as the lungs, to other organs, including the central nervous system. As such, Nocardia are capable of generating disease at different body sites, including abscesses in the brain [ 2 ]. Although Nocardia infections are primarily seen in patients with immunodeficiency, AIDS, cancer and diabetes [ 3 ], cases have been reported in individuals with fully functioning immune systems [ 4 ].…”
Section: Introductionmentioning
confidence: 99%